1999
DOI: 10.1046/j.1420-9101.1999.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalizing Harmonia axyridis (Coleoptera: Coccinellidae) larvae use endogenous cues to avoid eating relatives

Abstract: Cannibalism is widespread among many different organisms, and can have both negative and positive fitness consequences. Avoiding eating relatives can minimize negative fitness consequences of cannibalism. Such avoidance requires kin discrimination, but evidence for this ability among cannibals is limited with little data that address the cues used in such discrimination. We examined whether larvae of the ladybird beetle Harmonia axyridis avoid eating their relatives. We further manipulated environmental factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 19 publications
(28 reference statements)
1
40
0
Order By: Relevance
“…The former found a frequency of 25% for sibling cannibalism and 36% for nonsibling cannibalism, which were not significantly different. As for Joseph et al (1999), they showed that third instar larvae are less prone to cannibalize their siblings than nonsiblings (approximately 1:2). More recently, Michaud (2003) compared the cannibalism of first instar larvae in H. axyridis and found that siblings were less cannibalized than nonsiblings.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The former found a frequency of 25% for sibling cannibalism and 36% for nonsibling cannibalism, which were not significantly different. As for Joseph et al (1999), they showed that third instar larvae are less prone to cannibalize their siblings than nonsiblings (approximately 1:2). More recently, Michaud (2003) compared the cannibalism of first instar larvae in H. axyridis and found that siblings were less cannibalized than nonsiblings.…”
Section: Resultsmentioning
confidence: 97%
“…Hare and Eisner (1995) specifically addressed the subject in Utetheisa ornatrix, an arctiid moth, where no recognition was found. More recent papers tested specifically for kin recognition in several different taxa; however the results are conflicting even for the same species, as exemplified by the studies of Osawa (1989) and Joseph et al (1999) both with Harmonia axyridis (Coleoptera). The former found a frequency of 25% for sibling cannibalism and 36% for nonsibling cannibalism, which were not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…However, males ate as many of their own eggs as eggs sired by other males (perhaps because males invest much less energy in eggs and cannot safely distinguish them). Joseph et al (1999) found that third instar Har. axyridis placed together were much less likely to cannibalize siblings than unrelated individuals.…”
Section: Consumption Of L Arvaementioning
confidence: 99%
“…Although the disadvantages of consuming one's kin has been considered (Osawa 1992;Joseph et al 1999) those associated with eating toxic eggs of other species, although well described (Agarwala & Dixon 1992), has been ignored. The larvae of Adalia bipunctata (L.) and Coccinella septempunctata L., which regularly co-occur in the field, are reluctant to eat conspecific eggs painted with water extracts of whole eggs of the other species, and larvae of C. septempunctata are more likely to develop more slowly and/or die after eating a few eggs of A. bipunctata than 6ice 6ersa (Agarwala & Dixon 1992;Hemptinne et al 2000).…”
Section: Introductionmentioning
confidence: 99%